2014
DOI: 10.2478/pjvs-2014-0007
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Th1 and Th2 cytokine concentrations in ileal Peyer’s patches in gilts exposed to zearalenone

Abstract: GALT induces tolerance to foreign food antigens and plays an important role in the development of food allergies and the inflammatory bowel disease. The immune function of GALT is significantly influenced by an equilibrium between Th1 and Th2 subpopulations and the cytokines they produce. Th1 cytokines participate in the induction of a cell-mediated immune response, whereas Th2 cytokines induce powerful antibody-mediated responses. Changes in Th1/Th2 cell polarization of an immune response are associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 29 publications
1
23
1
Order By: Relevance
“…Marin et al (2013) administered ZEN to piglets at a dose of 316 ppb and observed that the mycotoxin was capable of inducing an inflammation in the bloodstream by increasing the production of proinflammatory cytokines. Similar findings were reported by Obremski (2014) who noted an increase in IFN-a levels in ileal Peyer's patches in pigs receiving 100 ppb of ZEN. Stimulation of cells of the innate immune system (NEUT, EOS) can also lead to the production of mediators of oxidative stress, which disrupts cell homeostasis and the maintenance of immunocompetence (Yu et al 2009).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Marin et al (2013) administered ZEN to piglets at a dose of 316 ppb and observed that the mycotoxin was capable of inducing an inflammation in the bloodstream by increasing the production of proinflammatory cytokines. Similar findings were reported by Obremski (2014) who noted an increase in IFN-a levels in ileal Peyer's patches in pigs receiving 100 ppb of ZEN. Stimulation of cells of the innate immune system (NEUT, EOS) can also lead to the production of mediators of oxidative stress, which disrupts cell homeostasis and the maintenance of immunocompetence (Yu et al 2009).…”
Section: Discussionsupporting
confidence: 78%
“…Interleukin-3 and IL-5 stimulate the production of eosinophils in the bone marrow and prolong their lifespan in peripheral tissues. In an in vitro study, ZEN provoked EL4 cells (thymoma cell line) to secrete IL-2 and IL-5 (Marin et al 1996), as in an in vivo study, the mycotoxin stimulated the release of IL-2 in ileal Peyer's patches in gilts (Obremski 2014). The observed increase in the numbers of neutrophilic and acidophilic granulocytes during ZEN-induced mycotoxicosis indicates that ZEN probably elicits an inflammatory response.…”
Section: Discussionmentioning
confidence: 87%
“…ZEN is a mycoestrogen which, in addition to its widely established hyperestrogenic activity, is capable of modulating the immune response towards the anti-inflammatory state (Obremski 2014). The above is manifested by increased secretion of IL-2 and IFN-γ (Marin et al 2013) and an intensified cytotoxic response characterized by a drop in the population of B cells and an increase in the population of cytotoxic CD8+ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…The applied method of isolating immunocompetent cells from ileal Peyer's patches supported the acquisition of a wide range of Th lymphocytes (CD4+CD8-), cytotoxic T lymphocytes (CD4-CD8+), B lymphocytes (B 1 , CD21+), memory cells (CD4+CD8+), NK cells and macrophages (adherent cells, data not published) for in vitro cultures and the control of the rate of changes in cell populations under physiological conditions (group C) and under exposure to ZEN (group E) throughout the experiment (Obremski et al 2014).…”
Section: Discussionmentioning
confidence: 99%